Non-contiguous finished genome sequence and description of Anaerococcus senegalensis sp. nov. Issue 1 (January 2012) - Lagier, Jean-Christophe; Karkouri, Khalid; Nguyen, Thi-Tien; Armougom, Fabrice; Raoult, Didier; Fournier, Pierre-Edouard
Abstract Anaerococcus senegalensis strain JC48T sp. nov. is the type strain ofA. senegalensis sp. nov. a new species within the genusAnaerococcus . This strain whose genome is described here was isolated from the fecal flora of a healthy patient.A. senegalensis is an obligate anaerobic coccus. Here we describe the features of this organism together with the complete genome sequence and annotation. The 1, 790, 835 bp long genome (1 chromosome but no plasmid) contains 1, 721 protein-coding and 53 RNA genes including 5 rRNA genes